2001
DOI: 10.1039/b101497h
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for weak base site participation in the vapour phase methylation of catechol over solid base catalysts

Abstract: The vapour phase alkylation of catechol over supported caesium catalysts gives good selectivity to guaiacol formation, and TPD studies indicate that this result can be correlated with the presence of weak basic sites on the catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…As far as the selectivity is concerned, CH 3 OH shows a higher selectivity for guaiacol formation initially as compared to DMC, but they both remain more or less steady with time on stream. In our earlier study on the methylation of catechol over solid base catalysts, we had proposed that the presence of weak basic sites over the base catalysts were important for the formation of oxygen-alkylated products [6]. A few papers on alkylation of catechol over base catalysts have also suggested that the basic sites are responsible for the formation of O-/ C-alkylated products [4,22].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As far as the selectivity is concerned, CH 3 OH shows a higher selectivity for guaiacol formation initially as compared to DMC, but they both remain more or less steady with time on stream. In our earlier study on the methylation of catechol over solid base catalysts, we had proposed that the presence of weak basic sites over the base catalysts were important for the formation of oxygen-alkylated products [6]. A few papers on alkylation of catechol over base catalysts have also suggested that the basic sites are responsible for the formation of O-/ C-alkylated products [4,22].…”
Section: Resultsmentioning
confidence: 98%
“…In recent years, several solid acid catalysts have been tried out for various alkylation reactions. Some of the solid acid catalysts studied for the title reaction were metal oxides [4][5][6][7][8][9], phosphates [10,11], ammonium metatungstate [12] and zeolites [13]. However, information on the alkylation of catechol over sulphatemodified zirconia (SZ) is rather limited [14,15] The surface areas of zirconia and sulphated zirconia samples were measured by Quantasorb AS-1 using N 2 as a probe molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Various heterogeneous catalysts have been investigated in vapour-phase methylation of catechol with methanol, including metal oxides [6,7], sulphates [2], metal phosphates [5,8,9], and supported heteropoly acids [10]. In general, the catalytic performance of these catalysts is greatly affected by the operation conditions, catalyst structures, acid and/or base properties.…”
Section: Introductionmentioning
confidence: 99%
“…The vapor-phase O-methylation of catechol with methanol to produce guaiacol has attracted much attention because it is economically and environmentally friendly for the industrial application [24][25][26][27]. Different kinds of materials have been investigated as catalysts for this reaction, including metal oxides [24,25], zeolites [26] and supported heteropoly acids [27].…”
Section: Introductionmentioning
confidence: 99%
“…The vapor-phase O-methylation of catechol with methanol to produce guaiacol has attracted much attention because it is economically and environmentally friendly for the industrial application [24][25][26][27]. Different kinds of materials have been investigated as catalysts for this reaction, including metal oxides [24,25], zeolites [26] and supported heteropoly acids [27]. Recently, we have found that the aluminophosphatebased materials, prepared by conventional precipitation method [28][29][30] and by citric acid route [11], have shown the catalytic potential in this vapor-phase reaction due to their suitable weak acid-base properties, and that the catalytic performance of the aluminophosphate-based catalysts is greatly dependent on the P/Al ratio and the synthetic method, which could affect the structures, specific surface areas and surface acid-base properties of these catalysts [11,30].…”
Section: Introductionmentioning
confidence: 99%